Differences in marital status and mortality by race/ethnicity and nativity among California cancer patients. Issue 10 (11th April 2016) - Martínez, María Elena; Anderson, Kristin; Murphy, James D.; Hurley, Susan; Canchola, Alison J.; Keegan, Theresa H. M.; Cheng, Iona; Clarke, Christina A.; Glaser, Sally L.; Gomez, Scarlett L.
Abstract : BACKGROUND: It has been observed that married cancer patients have lower mortality rates than unmarried patients, but data for different racial/ethnic groups are scarce. The authors examined the risk of overall mortality associated with marital status across racial/ethnic groups and sex in data from the California Cancer Registry. METHODS: California Cancer Registry data for all first primary invasive cancers diagnosed from 2000 through 2009 for the 10 most common sites of cancer‐related death for non‐Hispanic whites (NHWs), blacks, Asians/Pacific Islanders (APIs), and Hispanics were used to estimate multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) for marital status in relation to overall mortality by race/ethnicity and sex. The study cohort included 393, 470 male and 389, 697 female cancer patients and 204, 007 and 182, 600 deaths from all causes, respectively, through December 31, 2012. RESULTS: All‐cause mortality was higher in unmarried patients than in married patients, but there was significant variation by race/ethnicity. Adjusted HRs (95% CIs) ranged from 1.24 (95% CI, 1.23‐1.26) in NHWs to 1.11 (95% CI, 1.07‐1.15) in APIs among males and from 1.17 (95% CI, 1.15‐1.18) in NHWs to 1.07 (95% CI, 1.04‐1.11) in APIs among females. All‐cause mortality associated with unmarried status compared with married status was higher in US‐born API and Hispanic men and women relative to their foreign‐born counterparts. CONCLUSIONS: For patients who have the cancers that contribute most to mortality, being unmarried is associated with worse overall survival compared with being married, with up to 24% higher mortality among NHW males but only 6% higher mortality among foreign‐born Hispanic and API females. Future research should pursue the identification of factors underlying these associations to inform targeted interventions for unmarried cancer patients. Cancer 2016;122:1570–8 . © 2016 American Cancer Society . Abstract : Not being married at the time of cancer diagnosis is associated with higher all‐cause mortality compared with being married, but the association varies by race/ethnicity, sex, and nativity. Given the rising proportion of unmarried individuals in the United States and the variation by race/ethnicity, the contribution of marital status to the overall burden of cancer mortality will likely continue to rise.